Effectiveness of the PISA-DigiPjBL Model in Enhancing Scientific Literacy, Critical Thinking Skills, and Deep Learning of Physics Education Students - Mawarni Saputri; Musdar Musdar; Fadiya Haya (Universitas Pendidikan Mandalika, 2026)
This study examines the effectiveness of the PISA-DigiPjBL learning design in enhancing scientific literacy, critical thinking skills, and deep learning among undergraduate Physics Education students. A quasi-experimental study with a non-equivalent control group design was conducted involving 69 students enrolled in a Static Fluids course at Universitas Syiah Kuala, consisting of an experimental group (35 students) and a control group (34 students). The experimental group engaged in PISA-oriented digital project-based learning supported by a virtual laboratory, while the control group implemented conventional project-based learning supported by physical laboratory activities without digital integration. Accordingly, the findings are interpreted as the effect of an integrated PISA-oriented digital project-based learning environment rather than a single instructional component. Scientific literacy and critical thinking skills were measured using validated essay-based tests, while deep learning was assessed through a structured observation sheet capturing students’ learning behaviors during instructional activities. Content validity for all instruments was established through expert judgment, and reliability analyses indicated high internal consistency for the tests and excellent inter-rater agreement for the observation instrument. Data were analyzed using normality and homogeneity tests followed by independent sample t-tests. The results show that the experimental group achieved significantly higher gains in scientific literacy and critical thinking skills than the control group (α = 0.05), with large effect sizes (Cohen’s d = 1.30 for scientific literacy and 1.17 for critical thinking). Observational data further indicate that students in the experimental group demonstrated very high levels of deep learning behaviors, characterized by active engagement and collaboration, critical problem solving, creativity and innovation, and real-world application of physics concepts. These findings suggest that the PISA-DigiPjBL learning design is effective in promoting meaningful and deep learning in physics education at the higher education level when PISA-oriented project-based learning is integrated with digital learning environments.